1999
DOI: 10.1080/016909699386266
|View full text |Cite
|
Sign up to set email alerts
|

Processing of Reference and the Structure of Language: An Analysis of Complex Noun Phrases

Abstract: Five experiments used self-paced reading time to examine the ways in which complex noun phrases (both conjoined NPs and possessive NPs) in uence the interpretation of referentially dependent expressions. The experimental conditions contrasted the reading of repeated names and pronouns referring to components of a complex NP and to the entire complex NP. The results indicate that the entity introduced by a major constituent of a sentence is more accessible as a referent than the entities introduced by component… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
83
0
4

Year Published

2006
2006
2017
2017

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 68 publications
(99 citation statements)
references
References 31 publications
5
83
0
4
Order By: Relevance
“…Perhaps the biggest difference was the length of the passages; the earlier Glanzer experiments typically used longer experimental passages (usually consisting of eight sentences each) than did ours. Our choice of passages was determined by the ready availability and detailed character-isation of a set of narratives that had been used in several studies of coreference in our lab (Gordon, Hendrick, Ledoux, & Yang, 1999;Gordon & Scearce, 1995). These passages included a direct, well-controlled manipulation of dependency that allowed a comparison of the effects of interruption on more-and less-dependent passages in a concurrent study, the results of which are described elsewhere (Ledoux, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…Perhaps the biggest difference was the length of the passages; the earlier Glanzer experiments typically used longer experimental passages (usually consisting of eight sentences each) than did ours. Our choice of passages was determined by the ready availability and detailed character-isation of a set of narratives that had been used in several studies of coreference in our lab (Gordon, Hendrick, Ledoux, & Yang, 1999;Gordon & Scearce, 1995). These passages included a direct, well-controlled manipulation of dependency that allowed a comparison of the effects of interruption on more-and less-dependent passages in a concurrent study, the results of which are described elsewhere (Ledoux, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…Finally, the less prominent character (the tiger in Table 2) was introduced in a genitive noun phrase in the last context sentence. Introducing a referent in a genitive noun phrase decreases its discourse prominence in adult comprehension (Badecker and Straub, 2002;Gordon, Hendrick, Ledoux, and Yang, 1999). Using a genitive noun phrase also allowed us to remove the secondary character from sentencefinal position, reducing any countervailing effect of recency of mention.…”
Section: Methodsmentioning
confidence: 99%
“…Studies of intersentential coreference have shown that the repeated-name penalty is greater when the antecedent is the subject of the preceding sentence than when it is the object (Gordon et al, 1993;Gordon & Chan, 1995;Kennison & Gordon, 1997). Studies of both intersentential and intrasentential coreference have shown that the repeated name penalty is greater when the antecedent is the head noun than when it is embedded in a conjunct or when it is a possessive (Gordon, Ledoux, & Hendrick, 1997). The importance of syntactic prominence that emerges from studies of judgment and reading time is corroborated by results obtained on natural-language copora using syntax-based algorithms for pronoun resolution.…”
Section: Effects Of Syntactic Prominence On Coreferencementioning
confidence: 99%